Avaliação do desempenho de iluminação natural no protótipo de casa popular eficiente da UFSM - Souza, Matheus Cargnelutti de (2016)
The Brazilian population observed a possibility of credit concession for civil construction, not long time ago, due to Minha Casa Minha vida program. In opposition to this high demand of popular housing there are constructive techniques which are outdated concerning the quality of the built environment and the powerful efficiency of the new structures. Thus, in December 2013, it was introduced a prototype of a sustainable house in Centro de Eventos da Universidade Federal de Santa Maria (UFSM), and it was developed from the project of Casa Popular Eficiente, in a partnership between these institutions; UFSM and Universidade Luterana do Brasil (ULBRA). This dissertation originated with the purpose of evaluating the luminous performance of this prototype. Through the white paper method, it was accomplished mediations with portable Lux Meter in 260 reflected illuminance spots in order to obtain the reflectance of internal surfaces inside the buildings. It was used the program Rhinoceros with the plugin Diva installed in its environment. Hence, applying 1.240 sensors virtually inside the prototype, dynamics parameters of natural illuminance behavior were evaluated by performance tests based on NBR 15.575-1 and IESNA indicators. The prototype was also evaluated by prescriptive methods and simulation for the natural illuminance of RTQ-R. Some simulations with the change of reflectance levels in some prototype surfaces were performed. The main results are that the prototype fulfills dynamically the minimum, intermediate and superior illuminance requirements of NBR 15.575-1 natural illuminance. Hence, during the evaluation by the RTQ-R all the environments with extended permanence and the kitchen / laundry room satisfy dynamically the simulation requirements, as well as, the prescriptive test about the depth environments with natural illuminance originating from sideway opening. However, the prototype does not meet the requirements of the minimum level of 60% ceiling reflectance and only the kitchen / laundry room fulfills the minimum of 12, 5% floor area designed for the opening of the access of natural illuminance into the prototype. Therefore, the PCPE had a good result in the performance evaluation of natural illuminance, however the compact sizing which presents itself because it refers to a social interest habitation (habitação de interesse social - HIS), and the presence of low rates of reflectance indicates the possibility of an improvement in the established standards by the Brazilian rules regarding natural illuminance.